PENGARUH PEMBIAYAAN USAHA MIKRO, KECIL, MENENGAH (UMKM), DAN KECUKUPAN MODAL TERHADAP KEMAMPUAN MENDAPATKAN LABA DARI ASET PERBANKAN SYARIAH DI INDONESIA - Afkar, Taudlikhul (Universitas Negeri Surabaya, 2017)
The purpose of this research is to know the influence of sharia financing by the real sector through micro, small and medium enterprises (SMEs) and the influence of capital adequacy of Islamic Banking in Indonesia in order to earn profit by using managed assets. This study uses a quantitative approach that analyzes secondary data from financial statements Islamic Banking in Indonesia period 2012-2015. Sampling technique using purposive sampling with the ratio of each variable as a unit of analysis. The analysis used multiple linear regression with t test partially. The results showed that the influence of Islamic financing of micro, small and medium enterprises (SMEs) on the ability to get a very significant profit partially by 0.708 or 70.8%, while the influence of capital adequacy as measured by Capital Adequacy Ratio (CAR) -0.519 or -51.9%. The Effect of micro, small and medium enterprises (SMEs) financing and Capital Adequacy of Islamic Banking in obtaining profit amounts to 55.7%. This research shows that the financing of UMKM given by Islamic Banking gives an important role for entrepreneurs to develop his business with sharia scheme.Â